Formulasi Hukum Perlindungan Pasien Dalam Malpraktek Medik - Sri Wulandari; Zabidin Zabidin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Health is a human right and one of the elements of human welfare that must be realized by the state, the 1945 Constitution of the Republic of Indonesia, Article 34 paragraph (3) emphasizes that the state is responsible for providing equitable and affordable health service facilities for the entire community. This study aims to determine and analyze the legal formulation of patient protection in medical practice, using the normative legal research method, namely through literature/legislation searches (statute approach) with types of data sources, secondary data supported by primary data. The descriptive research type is then analyzed and presented qualitatively. The high level of public awareness of the importance of health has made people increasingly aware and understand their rights as patients in order to obtain good health services from health workers and hospitals. The legal relationship between doctors and patients as regulated in Law No. 17 of 2023 concerning Health is a business agreement relationship (inspaning verbentenis), which gives rise to rights and obligations. The community/patients receiving medical practice services have the right to legal protection so that every mistake in carrying out the medical profession is a form of mistake/violation of the law that is worthy of being prosecuted/filed in court as a form of protection for patients, victims of medical malpractice.